Interleukin-6 Reduction as a Predictor of Functional Capacity Improvement after Phase II Cardiac Rehabilitation Programme in Coronary Artery Bypass Surgery Patients - Ferhat E.S, Muhammad; Safri, Zainal; Sarastri, Yuke (CoinReads Media Prima, 2024)
Introduction: Improved functional capacity is a good prognostic value in patients after CABG. Phase II cardiac rehabilitation provides beneficial effects on physical function, cardiopulmonary function, inflammatory response, autonomic function, and improves functional capacity, and there is a significant decrease in Interleukin-6 values in patients after CABG. Several studies have selected Interleukin 6 as an inflammatory cytokine that can be used to assess the beneficial effects of cardiac rehabilitation in coronary heart disease conditions. The aim of the study was to determine the relationship of Interleukin-6 value as a predictor of functional capacity improvement after phase II cardiac rehabilitation in patients undergoing CABG. Method: This study was analytic observational study conducted retrospectively on 31 CABG patients who underwent phase II cardiac rehabilitation. Data collection on functional capacity, Interleukin-6 examination before and after phase II cardiac rehabilitation. Data were analyzed univariately and bivariately to assess the relationship between Interleukin-6 and functional capacity. Multivariate analysis will then be performed using linear regression. The relationship test will be performed with Pearson correlation test. Statistical data analysis using SPSS software, p value <0.05 is statistically significant. Results: There were 29 samples. The results of the cardiac exercise test showed an increase in distance at the end of phase II cardiac rehabilitation compared to the initial examination (457,655 ± 24,346 vs 180,482 ± 13,941). At the end of the examination there was a decrease in the average Interleukin-6 level from 24.412 ± 2.516 to 13.647 ± 1.413. There was a significant relationship between improvement in functional capacity and Interleukin-6 (p=0.032, r=0.40). An increase of 1 MET will decrease Interleukin-6 by 2.238 pg/mL. There was a decrease in mean Interleukin-6 from 24,412±2,516 to 13,647±1,413 at the end of phase II with p value <0.001. Conclusion: Interleukin-6 can be a predictor of improved cardiac functional capacity after phase II cardiac rehabilitation program in patients undergoing CABG.